2021
DOI: 10.3390/math9212706
|View full text |Cite
|
Sign up to set email alerts
|

Association Rules Mining for Hospital Readmission: A Case Study

Abstract: As an indicator of healthcare quality and performance, hospital readmission incurs major costs for healthcare systems worldwide. Understanding the relationships between readmission factors, such as input features and readmission length, is challenging following intricate hospital readmission procedures. This study discovered the significant correlation between potential readmission factors (threshold of various settings for readmission length) and basic demographic variables. Association rule mining (ARM), par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…They showed that the generated association rules could increase the overall efficiency of the recommender system. More recently, Miswan et al [16] proposed a framework of association rule mining in readmission tasks. The proposed framework consisted of two processes, namely data pre-processing and rule mining extraction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the generated association rules could increase the overall efficiency of the recommender system. More recently, Miswan et al [16] proposed a framework of association rule mining in readmission tasks. The proposed framework consisted of two processes, namely data pre-processing and rule mining extraction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, a common weakness that can be found in the most of above-described approaches [7][8][9][10][11][12][13][14][15][16][17][18] stands on the use of traditional algorithms, such as Apriori and FP-Growth. This drawback is due to the narrow applicability of these algorithms and the huge number of generated association rules [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it is witnessed that they are definitely unsuitable for dynamic environments, where new incoming changes are received continuously at runtime and may wrongly take decisions based on rules defined a priori. Apart from these limitations, a common limitation of previous approaches was that certain of them, as [Miswan et al, 2021], require domain expert intervention to validate the generated rules.…”
Section: Rule Learning Approaches Discussionmentioning
confidence: 99%
“…• Generating a redundant and large number of rules • Generating a redundant and large number of rules [Asadianfam et al, 2020] • Generating a redundant and large number of rules • Generating a redundant and large number of rules [Miswan et al, 2021] • Generating a redundant and large number of rules…”
Section: Rule Learning Approaches Discussionmentioning
confidence: 99%
See 1 more Smart Citation